The Influence of Long-Range Surface Forces on the Contact Angle of Nanometric Droplets and Bubbles - Stocco, Antonio (Langmuir : the ACS journal of surfaces and colloids, 2015)
For a droplet or a bubble of dimensions below 100 nm, long-range surface forces such as long-range van der Waals forces can compete with capillarity, which leads to a size dependence of the contact angle. This is discussed in this work, where we also show that the effect cannot simply be described by a normalized line tension. We calculate interfacial profiles for typical values of van der Waals forces and discuss the role of long-range surface forces on the contact angle of nanobubbles and nanodrops